Enhanced oxygen reduction reaction of LaSrCoO4–Ce0.9Mn0.1O2 composite cathode for solid oxide fuel cells. Issue 6 (15th March 2023) - Wu, Ke; Fu, Lei; Zhou, Jun; Zhou, Likai; Yang, Jiaming; Liu, Zhengrong; Zhao, Hongfei; Deng, Qinyuan; Wu, Kai
Abstract: The development of high-performance cathodes with low polarization resistance and good tolerance to CO2 are important issues for solid oxide fuel cells (SOFC). In this work, we synthesized LaSrCoO4 –Ce0.9 Mn0.1 O2 (LSCO4-CMO) composite cathode materials by the citric acid-nitrate method. The composite cathode sintered at 950 °C for 4 h shows large porous morphology and superior electrochemical activity of oxygen reduction reaction (ORR). Electrochemical properties analysis suggests that LSCO4-35 wt% CMO (L-35C) exhibits the lowest polarization resistance (Rp ) at 800 °C and the value of Rp is 0.14 Ω cm 2 which is far lower than that of pure LSCO4 (0.77 Ω cm 2 ). It is found that the LSCO4-CMO has unique microstructure and more active sites for ORR. Moreover, the doping of CMO offers more oxygen ions transport channels as the concentration of oxygen vacancies increases. The study of the effect of oxygen partial pressure on Rp reveals that as the temperature rises, the rate of dissociation of oxygen molecules is significantly accelerated, indicating that the charge transfer of oxygen atoms becomes the main rate-limiting step. A high oxygen reduction catalytic activity and excellent CO2 tolerance were demonstrated in L-35C by O2 -TPD and CO2 -TPD tests, making LSCO4-CMO a potential candidate for SOFC cathode.